Nutrient addition shifts plant community composition towards earlier flowering species in some prairie ecoregions in the U.S. Central Plains - Biederman, Lori (2017)
Fil: Biederman, Lori. Iowa State University. Department of Ecology, Evolution and Organismal Biology. Ames, Iowa, United States of America.